Evaluation of leukocyte depletion of packed red blood cell units and impact on clinically observed transfusion reactions - Steblaj, Barbara; Galli, Jasmin; Torgerson, Paul; Kutter, Annette (Frontiers in Veterinary Science, 2023)
Introduction The aim of this retrospective study was to determine whether there is an association between leukoreduction of packed red blood cell (pRBC) units and reduction of clinically observed transfusion reactions (TR), particularly febrile non-haemolytic transfusion reactions (FNHTR), and better outcomes in dogs. Secondary aims were to evaluate the effects of other factors suspected to influence transfusion reaction frequency or survival, including crossmatching, use of immunosuppressive drugs, and age and number of the blood products being administered. Materials and methods Medical data on dogs transfused with leukocyte-reduced (LR) and non-leukocyte-reduced (N-LR) pRBC units at the Animal Hospital Zürich, University of Zürich, Switzerland between January 1, 2007, and December 17, 2018 were searched. Before 2014, only N-LR blood were transfused. After 2014, both LR and N-LR blood were available. Results A total of 339 canine patients were transfused with 413 pRBC units; 30.5% (126/413) were LR units and 69.5% (287/413) were N-LR. Data collected from medical records was analyzed using univariate and multivariate logistic regression. In the present study, TR occurred in 19.8% of pRBC units (25/126) with LR and in 17.7% (51/287) of pRBC with N-LR; p > 0.05. FNHTR occurred in 6.3% of pRBC units (8/126) with LR and in 4.5% (13/287) of those with N-LR; p > 0.05. There was no correlation between the occurrence of TR and discharge from hospital (p > 0.05). Crossmatching, immunosuppressive therapy, and age of the blood product were not associated with the frequency of TR; p > 0.05 for all. The duration of survival days was not related to the number of transfusions dogs received. Discussion In the present study, the leukocyte-depletion of transfused pRBC units was not associated with fewer TR nor to fewer FNHTR compared to N-LR units. Discharge of dogs from hospital was not dependent on the occurrence of TR.